Coagulation and flocculation effects in the purification of tannery waste solutions - Danylkovych, Anatoliy; Sanginova, Olga; Tolstopalova, Nataliia; Obushenko, Tetiana; Yavorskiy, Dmytro (Technologies and Engineering, 2025)
Available methods of wastewater treatment of tanneries require improvement to ensure the desired efficiency of purification and regeneration of valuable components contained in the waste process solutions. The purpose of this study was to provide a comprehensive coagulation-flocculation treatment of liquid waste from tanneries using mathematical modelling methods. The study conducted experimental investigation of the effectiveness of coagulants – aluminium sulphate and iron (III) chloride – and flocculants: polyhexamethylene guanidine hydroxychloride and its acetate, as well as reagent P228. The effect of pH on the coagulation process was examined. The efficiency of the coagulation process was evaluated by an integral indicator - the degree of purification, which was determined considering the turbidity and optical density of the purified water samples. The study presented the findings on coagulation and flocculation effects that occur during the purification of samples of tannery waste process solutions after the filling-fattening and dyeing processes. The studied samples are characterised by high concentrations of sulphates (over 9,000 mg/dm3) and chlorides (over 1,500 mg/dm3), an increased content of suspended solids (over 843 mg/dm3) and metal ions: chromium (III), iron, and aluminium. According to the findings of the study, the aluminium-based coagulant is more efficient than the iron-based coagulant. Among the flocculants, polyhexamethylene guanidine hydroxychloride is the most effective, while the pH value should be 10. The results of experimental studies were used to obtain a mathematical model that described the coagulation process with a sufficient degree of accuracy. The results of mathematical modelling can be used to calculate the optimum parameters of the coagulation process.